How do the leading European IT Services firms, align their strategic structures in order to take account of the significant market needs, whilst avoiding problems caused by the predicted cyclical downturns? - Copland, Richard (2005)
The boom in the year 2000 brought unprecedented growth for the IT Services industry, which was then followed by a seemingly unforeseen slump as organizations across the globe sort to gain returns form there investments. The impact on the IT Services firms was profound as many firms underwent costly restructuring programs in order to align to the market requirements of the time. As firms begin to experience growth, one of the challenges facing executives is how to organize their strategic structures so as to accommodate the changes in the predicted demand cycles, without similar repercussions. Such opportunities need to incorporate the new environmental dynamics as firms have grown their service offerings, to the ever more demanding clients, through vertical integration. Notwithstanding the increase in service offerings, the options for executives are multiplied as the rise of new competitors in new locations across the globe, born part out of the excesses of the previous boom present themselves as increasingly viable competitors. Therefore given such changing market dynamics one structural solution that lends itself to the nature of IT Service firms is the implementation of a Network structure, through which firms can continue to utilize their competencies gained from alliance generation.